John Wardroper, Lovers, Rakes and Rogues - Jaine, Tom (Petits Propos Culinaires, 2001)
John Wardroper, Lovers, Rakes and Rogues (Shelfmark Books, London, 1995: ISBN 0-9526093-0-4: 366 pp., p/b, £9.95).